Utilização de equações integrais no domínio do tempo na predição da propagação sobre terrenos irregulares - Rodrigo Bastos Vasconcelos Teperino (2003)
This work deals with the prediction of radio wave propagation over irregular terrains by using the integral equations in frequency and time domain. The implemented method allows an exact electromagnetic analysis. All existing couplings among sources and the terrain are considered in the solution, without any kind of approximation, exceptthose related to the numerical implementation. The terrain surface is assumed to be electrically smooth. By considering a grazing incident field with a vertical polarization, the surface can be treated as a perfect magnetic conductor. The surface transverse variation is disregarded. The Method of Moments (MoM) is employed in frequency domain in order to obtain equivalent currents on the terrain surface. These currents can be calculated recursively, as back-scattering effects are neglected. To perform this task, a considerable computational effort is demanded. The need of shorter processing times, especially when analyzing cases with either large surfaces or excessive number of segments, has motivatedthe application of an acceleration technique called Fast Far Field Approximation (FAFFA). This technique is based on the surface division in groups of segments. The interaction among segments is treated as an approximation of the interaction among groups. Cases over a wedge profile and a practical profile are analyzed. Two distinct approaches are adopted to obtain the time-domain results: the frequency-domain analysis plus the inverse Fourier Transform application and the direct time-domain analysis. In time domain, cases over a wedge profile and two consecutive wedges are considered